Evaluation of a collaborative operation to improve child sexual abuse reporting in Western Australian indigenous communities - Bailey, Cate (Criminal justice and behavior, 2015)
This study presents an evaluation of Operation RESET, a community engagement intervention designed to help remote Indigenous communities and human service agencies to uncover, respond to, and prevent child sexual abuse. The primary aim of this evaluation was to determine whether the intervention was associated with increased reporting. Data were obtained for six Western Australian regions between 2007 and 2012. Number of reports and arrests significantly increased in the intervention areas during the intervention compared with the pre-intervention time period but not in the control areas. Arrest rates significantly increased during the intervention and increased further following the intervention. There were no changes in arrest rates in regions that did not participate in the operation. This evidence suggests that the reforms led to a marked improvement in some key outcomes for Indigenous victims of child sexual abuse and supports the adoption of this collaborative approach by other jurisdictions.